Neuronal Tissue-Nonspecific Alkaline Phosphatase (TNAP) - Fonta, Caroline; Négyessy, László; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
Phosphatases such as TNAP are fundamental in regulating cellular, and consequently numerous body functions. TNAP is a ubiquitous enzyme with a wide spectrum of substrates and specificity regulation at the cellular level and the lack of TNAP activity is a lethal condition. Recent findings of a highly specific regional, laminar and subcellular localization of TNAP in the cerebral cortex indicates that in addition to its metabolic and skeletal functions, TNAP also plays a role in regulating cerebral functions, most probably cognition. In fact, TNAP disturbance could result in complex diseases such as epilepsy, developmental retardation and Alzheimer disease. Available data suggest that, regarding brain functions, TNAP is a potentially important target of clinical research. The proposed book aims to provide an overview of our current understanding of the functions of TNAP in the brain.
1 Clinical forms and animal models of hypophosphatasia -- 2 Molecular genetics of hypophosphatasia and phenotype-genotype correlations -- 3 Genetically modified mice for studying TNAP function -- 4 Tissue-Nonspecific Alkaline Phosphatase in the Developing Brain and in Adult Neurogenesis -- 5 Rediscovering TNAP in the brain: a major role in regulating the function and development of the cerebral cortex -- 6 TNAP in the retina -- 7 Tissue Non-specific Alkaline Phosphatase (TNAP) in vessels of the brain -- 8 What can we learn about the neural functions of TNAP from studies on other organs and tissues? -- 9 TNAP, an essential player in membrane lipid rafts of neuronal cells -- 10 Signal transduction pathways of TNAP: molecular network analyses -- 11 Vitamin B-6 Metabolism and Interactions with TNAP -- 12 Tetramisole and levamisole suppress neuronal activity independently from their inhibitory action on Tissue Non-Specific Alkaline Phosphatase in mouse cortex -- 13 TNAP and Pain Control -- 14 Neurological symptoms of Hypophosphatasia -- 15 Recombinant enzyme replacement therapy in hypophosphatasia -- 16 Neurogenetic Aspects of Hyperphosphatasia in Mabry Syndrome -- 17 The role of tissue non-specific alkaline phosphatase (TNAP) in Neurodegenerative diseases: Alzheimer’s disease in the focus -- 18 TNAP plays a key role in neural differentiation as well as in neurodegenerative disorders -- Index.
Keywords: Human physiology; Animal physiology; Developmental biology; Neurosciences; Human Physiology; Animal Physiology; Developmental Biology; Neurosciences